Shoulder terminal range eccentric antagonist/concentric agonist strength ratios in overhead athletes - Yildiz, Y.; Aydin, T.; Sekir, U.; Kiralp, M. Z.; Hazneci, B.; Kalyon, T. A. (Scandinavian Journal of Medicine & Science in Sports, 2006)
Objective: The agonist-antagonist strength relationship for shoulder external rotation and internal rotation was formerly described by the relatively more functional ratios of eccentric external rotator to concentric internal rotator moments, and eccentric internal rotator to concentric external rotator moments for the entire range of motion. The aim of this study was to provide descriptive data for terminal range eccentric antagonist/concentric agonist rotator cuff strength in overhead athletes.